The genetic variants at the HLA-DRB1 gene are associated with primary IgA nephropathy in Han Chinese - Jiyun Yang; Guisen Li; Li Zhu; Yi Shi; Jicheng Lv; Fang Lu; Xiaoqi Liu; Shi Ma; Cheng Jing; Ying Lin; Haiyan Wang; Li Wang; et al. (BMC, 2012)
Abstract Background Immunoglobulin A nephropathy (IgAN), an immune-complex-mediated glomerulonephritis defined immunohistologically by the presence of glomerular IgA deposits, is the most common primary glomerular disease worldwide and a significant cause of end-stage renal disease. Familial clustering of patients with IgAN suggests a genetic predisposition. Methods In this study, 192 patients with IgAN and 192 normal controls in the Sichuan cohort and 935 patients with IgAN and 2,103 normal controls in the Beijing cohort were investigated. HLA-DRB1*01-DRB1*10 specificities were genotyped by the PCR-SSP technique in both cohorts. Based on the HLA-DRB1*04-positive results, the subtypes of HLA-DRB1*04 were analyzed using sequencing-based typing (SBT) in 291 IgAN cases and 420 matched controls. Results The frequency of HLA-DRB1*04 in the IgAN group was significantly higher than that in the control group (0.129 vs. 0.092, P = 8.29 × 10-5, odds ratio (OR) =1.381, 95% confidence interval (CI) 1.178-1.619). Other alleles at the HLA-DRB1 locus were observed with no significant differences between the case and control groups. The dominant alleles of the HLA-DRB1*04 subtypes were DRB1*0405 in both cohorts. The frequencies of HLA-DRB1*0405 and 0403 were significantly increased in the patients compared to healthy subjects. Conclusion HLA-DRB1*04 was significantly associated with primary IgAN in Chinese population. This result implies that HLA-DRB1 gene plays a major role in primary IgAN.